Parental risk preferences, maternal bargaining power, and the educational progressions of children: Lab-in-the-field evidence from rural Côte d'Ivoire - Arnab K. Basu; Ralitza Dimova; Monnet Gbakou; Romane Viennet (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We analyse the effect of parental risk preferences and a novel measure of maternal bargaining power over educational expenses-elicited via lab-in-the-field experiments in rural Côte d'Ivoire-on the educational progression of boys and girls. Data from 135 couples and their children show that the father's risk aversion is negatively associated with school attendance for boys and lowers the likelihood of transition from no schooling to primary schooling for both boys and girls. The mother's risk aversion, on the other hand, has a positive association with the transition into primary schooling and a negative association with the transition into secondary schooling only for girls. The mother's bargaining power is also negatively associated with girls' schooling, while greater bargaining power for mothers who are relatively more risk averse than the father adversely impacts the transition into primary schooling for boys. Our findings are in line with suggestive evidence that points to a preference for current income generated by the employment of boys in high-value cash crop production and the concern for girls' safety associated with traveling long distances to attend secondary schools.
Keywords: C93; J43; O55; 330; risk preferences; bargaining power; educational progressions; Côte d'Ivoire; schooling